2011
DOI: 10.1094/cchem-09-10-0131
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Soft Wheat Flour Physicochemical Composition and Cookie‐Making Performance

Abstract: Cereal Chem. 88(2):130-136Nowadays in Argentina, cookies, crackers, and cakes are made of flour obtained from bread wheat with additives or enzymes that decrease the gluten strength but increase production costs. The present research work aims to study the relationship between flour physicochemical composition (particle size average [PSA], protein, damaged starch [DS], water soluble pentosans [WSP], total pentosans [TP], and gluten), alkaline water retention capacities behavior, solvent retention capacities pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 29 publications
4
44
0
3
Order By: Relevance
“…Damaged starch is another important parameter that determines the cookie making potential of the wheat varieties. In previous studies by Moiraghi et al (2011), greater damaged starch content was associated with lower cookie factor. In this study a similar trend was observed, the damaged starch was found to be negatively correlated ðr ¼ 20:536Þ with the cookie spread.…”
Section: Variation In Gluten Protein Compositionmentioning
confidence: 59%
“…Damaged starch is another important parameter that determines the cookie making potential of the wheat varieties. In previous studies by Moiraghi et al (2011), greater damaged starch content was associated with lower cookie factor. In this study a similar trend was observed, the damaged starch was found to be negatively correlated ðr ¼ 20:536Þ with the cookie spread.…”
Section: Variation In Gluten Protein Compositionmentioning
confidence: 59%
“…For soft wheat products, the effect of protein is due to water holding capacity, rather than formation of gluten networks. Protein quantity is generally not correlated with flour milling traits in soft wheat (Moiraghi et al 2011). Protein quantity and grain yield are negatively correlated in wheat but neither of those traits influenced our ability to detect QTL for milling, SRC, or end-use quality traits at the 3B locus so we believe that there is a direct effect on grain quality at that locus, apart from the effect on grain yield and protein content.…”
Section: Discussionmentioning
confidence: 77%
“…In the case of cookie-making with wheat flours, both their particle size and damaged starch content, and therefore the milling system, are key factors which determine the characteristics of the final product (Barak et al, 2014;Moiraghi et al, 2011;Yamamoto et al, 1996). This relationship can be due to the influence of these parameters on water absorption capacity of these flours and therefore dough rheology, as well as to structural effects.…”
Section: Particle Size Classificationmentioning
confidence: 99%